Office orthostatic blood pressure measurements and ambulatory blood pressure monitoring in the prediction of autonomic dysfunction - Alquadan, Kawther F. (Clin Hypertens, 2017)
BACKGROUND: In this retrospective analysis we investigated the predictive performance of orthostatic hypotension (OH) and ambulatory blood pressure monitoring (ABP) to predict autonomic dysfunction. METHODS: Statistical associations among the candidate variables were investigated and comparisons of predictive performances were performed using Receiver Operating Characteristics (ROC) curves. RESULTS: Ninety-four patients were included for analysis. No significant correlations could be demonstrated between OH and components of ABP (reversal of circadian pattern, postprandial hypotension and heart rate variability), nor between OH and autonomic reflex screen. Reversal of circadian pattern did not demonstrate significant correlation (r = 0.12, p = 0.237) with autonomic reflex screen, but postprandial hypotension (r = 0.39, p = 0.003) and heart rate variability (r = 0.27, p = 0.009) demonstrated significant correlations. Postprandial hypotension was associated with a five-fold (OR 4.83, CI95% 1.6–14.4, p = 0.005) increased risk and heart rate variability with a four-fold (OR 3.75, CI95% 1.3–10.6, p = 0.013) increased risk for autonomic dysfunction. Per ROC curves, heart rate variability (0.671, CI(95%) 0.53–0.81, p = 0.025) and postprandial hypotension (0.668, CI(95%) 0.52–0.72, p = 0.027) were among the best predictors of autonomic dysfunction in routine clinical practice. CONCLUSION: Postprandial hypotension and heart rate variability on ambulatory blood pressure monitoring are among the best predictors of autonomic dysfunction in routine clinical practice.